Real‐time Tissue Elastography for Assessment of Liver Stiffness in Adults Without Known Liver Disease. (18th September 2015) - Hu, Yu; Gong, Hai-Yan; Lin, Hong-Jun
Abstract : Objectives: To investigate normal liver stiffness and its influential factors in adults without liver disease using real‐time tissue elastography. The liver stiffness threshold value for identifying patients with chronic liver disease was also determined. Methods: One hundred twenty healthy volunteers were examined with real‐time tissue elastography. An integrated quantitative elastographic parameter, defined as the liver fibrosis index, was obtained by tissue dispersion quantitative analysis. Correlations between the liver fibrosis index and age, sex, and body mass index (BMI) were studied. To determine the threshold value for identifying chronic liver disease, 29 patients with chronic hepatitis B who underwent liver biopsy, including patients without fibrosis (fibrosis stage F0; n = 9) and patients with substantial fibrosis (F1–F2; n = 20) were also investigated. A receiver operating characteristic curve analysis for differentiating the F0 from the F1–F2 group was performed. Results: There were no significant differences in the mean liver fibrosis index between sexes or among different age groups. There was a positive correlation between BMI and the liver fibrosis index. The mean liver fibrosis index ± SD in healthy participants with a normal BMI was 1.31 ± 0.25. The mean liver fibrosis index values for F0 and F1–F2 patients with a normal BMI were 1.47 ± 0.24 and 2.44 ± 0.49, respectively ( P < .001). The optimal liver fibrosis index threshold value for discriminating normal liver from noncirrhotic chronic liver disease was 2.12 in participants with a normal BMI. Conclusions: Liver stiffness determined by real‐time tissue elastography in healthy Chinese adults is not affected by age and sex but has a positive correlation with BMI. Real‐time tissue elastography for assessment of liver stiffness can also be used for identification of substantial fibrosis in patients with chronic liver disease.